The AMP-Related Kinase (AMPK) Induces Ca2+-Independent Dilation of Resistance Arteries by Interfering With Actin Filament Formation. Issue 2 (7th July 2017) - Schubert, Kai Michael; Qiu, Jiehua; Blodow, Stephanie; Wiedenmann, Margarethe; Lubomirov, Lubomir T.; Pfitzer, Gabriele; Pohl, Ulrich; Schneider, Holger
Abstract : Rationale: : Decreasing Ca 2+ sensitivity of vascular smooth muscle (VSM) allows for vasodilation without lowering of cytosolic Ca 2+ . This may be particularly important in states requiring maintained dilation, such as hypoxia. AMP-related kinase (AMPK) is an important cellular energy sensor in VSM. Regulation of Ca 2+ sensitivity usually is attributed to myosin light chain phosphatase activity, but findings in non-VSM identified changes in the actin cytoskeleton. The potential role of AMPK in this setting is widely unknown. Objective: : To assess the influence of AMPK on the actin cytoskeleton in VSM of resistance arteries with regard to potential Ca 2+ desensitization of VSM contractile apparatus. Methods and Results: : AMPK induced a slowly developing dilation at unchanged cytosolic Ca 2+ levels in potassium chloride–constricted intact arteries isolated from mouse mesenteric tissue. This dilation was not associated with changes in phosphorylation of myosin light chain or of myosin light chain phosphatase regulatory subunit. Using ultracentrifugation and confocal microscopy, we found that AMPK induced depolymerization of F-actin (filamentous actin). Imaging of arteries from LifeAct mice showed F-actin rarefaction in the midcellular portion of VSM. Immunoblotting revealed that this was associated with activation of the actin severing factor cofilin. Coimmunoprecipitation experiments indicated that AMPK leads to the liberation of cofilin from 14-3-3 protein. Conclusions: : AMPK induces actin depolymerization, which reduces vascular tone and the response to vasoconstrictors. Our findings demonstrate a new role of AMPK in the control of actin cytoskeletal dynamics, potentially allowing for long-term dilation of microvessels without substantial changes in cytosolic Ca 2+ . Abstract : Supplemental Digital Content is available in the text.